Development of a beverage based on citric juice with the additionof whey - Rivero, Roy Cristian (2019)
Faced with new trends in healthy eating, the need arises to work to expand the market. The Argentine Society of Nutrition, based on local and international studies, suggests that an adequate intake of dairy products not only provides calcium, it also provides compounds associated with a decrease in the risk of chronic inflammatory diseases. The objective of this work is to formulate and develop beverages based on orange juice with addition of liquid and powdered whey, sweetened naturally, to study the physicochemical, nutritional and sensory characteristics. The samples were homogenized and pasteurized at 85°C for 30 minutes. pH, acidity, solids content and color were analyzed. A just-about-right (JAR) scale was used to evaluate the intensity level of acid taste, bitter taste, flavor, and color attributes; meanwhile a 5-points hedonic scale was used to evaluate global acceptability of samples. The intensity level analysis showed that the taste and color were "ideal". In global acceptability, it was observed that pleasure categories were more than 60% and only 10% considered it unpleasant. The beverage presented pH, color and solids content similar to citrus beverages further it was rated as pleasant for consumers.